The Effect of Accrual-Based Accounting Training and Assistance on the Knowledge Improvement of Financial Report Management at Local Government Units - Din, Muhammad; Paranoan, Selmita; Azdar, Faisal; Ralis, Galing (LifeSciFi, 2022)
This study aims to analyze the role of assistance in preparing the financial report to improve local government financial management by referring to Government Accounting Standards. This study was conducted at a regional apparatus organization (OPD/Organisasi Perangkat Daerah) in the Tojo Una Una’s Financial Management Agency (BPKAD/Badan Pengelolaan Keuangan dan Aset Daerah). The research was conducted with field activities through training to participants. The study evaluated the activity by comparing the results of the pre and post-test participants to assess the benefit. The tests were examined using the Compare Means Paired-Sample T-Test analysis with the Statistical Package for the Social Sciences (SPSS) statistical analysis tool. The results showed the difference between pre-test and post-test scores. These results show that before the administration material’s start, the expenditure’s treasurer received a lower pre-test score than the average post-test score after the material. It indicates that the material was delivered well, and there was the absorption of the material obtained by the community service participants. With the Government Accounting Standards, the financial reports of the central or local government will be of higher quality with the characteristics of understandable, relevant, reliable, and comparable. The findings encourage the reliable government’s financial statements to serve as both a tool of accountability and a basis for decision-making in the local government context.